Study on Quality Inspection and Anti-Seepage Performance Evaluation of Karst Underground Dam Curtain - ZHANG Kai; SU Zhengyang; LIU Chengdong; SHEN Guangze; JIAO Jie (Renmin Zhujiang)
There are many problems in the quality inspection and anti-seepage performance evaluation of karst underground dam's curtain because of its special structure and environment.Taking a typical karst underground dam seepage prevention system in southwest China as the research object,this paper identifies the distribution and weak parts of the anti-seepage curtain through the high-density resistivity method,further verifies the accuracy of results from high-density resistivity method through local water pressure test in borehole,and analyzes the composition and corrosion type of precipitates by precipitation thermogravimetry.This study provides a feasible plan for the current quality inspection and anti-seepage performance evaluation of karst underground dam,has a strong engineering reference significance for the popularization and application of karst underground dam and its safety assurance in the operation period,and also serves as an important reference for the establishment and improvement of the performance evaluation system and monitoring mechanism for the seepage control of underground reservoirs in karst areas.